2018
DOI: 10.1097/pec.0000000000001387
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Attitudes Toward Sexually Transmitted Infection Screening in the Emergency Department

Abstract: Objectives Adolescents who seek care in emergency departments (EDs) are often at high risk for sexually transmitted infections (STIs). The objective of this study was to assess adolescent attitudes towards ED-based STI screening. Methods We conducted a secondary analysis of a cross-sectional study that evaluated STI screening acceptability and prevalence when STI testing was universally offered to asymptomatic adolescents presenting to the ED for care. Adolescents 14–21 years old completed a computerized sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, urine chlamydia/gonorrhea testing can easily be collected with the urine pregnancy test. Studies have found that adolescents consider the ED an acceptable site for STI screening [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, urine chlamydia/gonorrhea testing can easily be collected with the urine pregnancy test. Studies have found that adolescents consider the ED an acceptable site for STI screening [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that most adolescents feel that the PED is an appropriate place to be asked about sexual history, regardless of their presenting chief complaint. 16,17 Studies have also shown that obtaining a sexual history increases the frequency of STI testing. 17 Of the patients for whom a history was taken, more than half (59.2%) were sexually active, indicating a definite need for screening in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although many aspects of STI testing/screening can be difficult to control (patients may not consent, for example), getting a sexual history is a controllable aspect of the treating physician's role. Research has demonstrated that most adolescents feel that the PED is an appropriate place to be asked about sexual history, regardless of their presenting chief complaint 16,17 . Studies have also shown that obtaining a sexual history increases the frequency of STI testing 17 …”
Section: Discussionmentioning
confidence: 99%